BOARD DIVERSITY, CAPITAL STRUCTURE, AND FIRM VALUE IN SERVICE COMPANIES LISTED IN INDONESIA STOCK EXCHANGE - Namla Elfa Syariati; Nurazizah Kadir (Jurnal Iqtisaduna, 2019)
As company ownerships were more diversified, so were the appointed boards. Thus, this study aimed to investigate whether these diversified boards could provide substantial push to the companies’ capital structure or even firm values. Using the data from 75 service companies, listed in Indonesia Exchange (IDX), we conducted two regression analysis and sobel test to examine the relationship of those variables. This study found that. The results showed that gender diversity on boards of directors negatively affect the capital structure, while the age and educational background in business economics and positive impact on the capital structure. Furthermore, gender diversity, and capital structure positively affects the value of the company. While age negatively affect the value of the company. Then the educational background does not affect the value of the company. In addition, this study also showed that the capital structure is not able to mediate the relationship between the diversity of gender, age and educational background of the value of the company.